The Potential of Neuregulin 4 as a Novel Biomarker and Therapeutic Agent for Vascular Complications in Type 2 Diabetes Mellitus - Dan X; Li K; Xu J; Yan P (Dove Medical Press, 2024)
Xiaofang Dan,1- 3 Ke Li,1- 3 Jiali Xu,4 Pijun Yan1- 3,5,6 1Department of Endocrinology and Metabolism, the Affiliated Hospital of Southwest Medical University, Luzhou, People's Republic of China; 2Metabolic Vascular Disease Key Laboratory of Sichuan Province, Luzhou, People's Republic of China; 3Sichuan Clinical Research Center for Diabetes and Metabolism, Luzhou, People's Republic of China; 4Department of Gastroenterology, the Affiliated Hospital of Southwest Medical University, Luzhou, People's Republic of China; 5Sichuan Clinical Research Center for Nephropathy, Luzhou, People's Republic of China; 6Cardiovascular and Metabolic Diseases Key Laboratory of Luzhou, Luzhou, People's Republic of ChinaCorrespondence: Pijun Yan, Email peter2007110361@126.comAbstract: Neuregulin 4 (Nrg4), a novel adipokine produced primarily by brown adipose tissue (BAT), has been functionally characterized to exert beneficial effects on modulating energy homeostasis and glucolipid metabolism, and is closely associated with the development and progression of obesity and obesity-associated metabolic diseases, such as type 2 diabetes mellitus (T2DM) and cardiovascular diseases. Recently, there has been a growing focus on the relationship between circulating Nrg4 levels and T2DM-related vascular complications. In this review, we discussed the known and potential roles of Nrg4 in various physiological and pathological processes, and its association with vascular complications in T2DM, in the aim of finding a potential biomarker recommended for the clinical diagnosis, prognosis and follow-up of T2DM patients at high risk of developing vascular complications as well as providing new therapeutic approaches.Keywords: neuregulin 4, adipokine, diabetes, type 2, vascular complications